Determinants of Iron Supplementation Adherence in Pregnancy and Their Implications for Maternal Health Outcomes: A Systematic Literature Review [Accepted] - Nurfaizah, Diza Ulya; Sari, Jayanti Dian Eka; Lestari, Endang (Health Dynamics, 2026)
Background: The maternal mortality rate in the world based on data from the World Health Organization (WHO) in 2017 was 817 people every day. Based on UNICEF data in 2020, the Infant Mortality Rate (IMR) in the world reached 2.5 million deaths before the age of one month. The Ministry of Health in 2020 estimated that in 2024 the MMR in Indonesia would reach 183/100,000 KH and in 2030 it would be 131/100,000 KH. Objective: This study aims to explore in depth the relationship between the consumption of iron tablets and the risk of maternal death. Method: Using a literature review method and searching for articles using the Preferred Reporting Items for Systematic Reviews & Meta-Analyses (PRISMA) method with inclusion and exclusion criteria, combining language keywords. The database used to search for articles is PubMed and Web of Science. Results: There are 5 articles that match the topic and can be used for a systematic literature review. Conclusion: Compliance of pregnant women in consuming iron tablets (Fe)  greatly influences the prevention of anemia during pragnency. So there is a relationship between the consumption of iron tabltes and the risk of maternal death.